Enhancing Students’ Critical Thinking Through Problem-Based Learning In Sine Rule Instruction: A Quasi-Experimental Study - Cahyani Novia Sari; Fadilatul Nikmah; Aji Restu Septian Arwanto; Endrayana Putut Laksminto Emanuel (Jurnal Pendidikan Matematika, 2026)
The purpose of this study is to evaluate how well the Problem-Based Learning (PBL) approach enhances students' critical thinking abilities when studying the law of sines. The study employed a quantitative methodology using a non-equivalent control group design, which is a quasi-experimental design. Two classes of high school students served as the research subjects: the experimental class, which got PBL-based instruction, and the control class, which employed traditional instruction. A descriptive test was used as the research tool to gauge critical thinking abilities using indications of interpretation, analysis, assessment, and inference. Effect size, N-Gain computation, and an independent sample t-test were used to examine the data. The findings demonstrated that students' critical thinking abilities in the experimental class and the control class differed significantly (p < 0.05). With a big effect size value, the improvement in students' critical thinking abilities in the experimental class fell into the moderate to high range. These results show that PBL is successful in helping students strengthen their critical thinking abilities, particularly when it comes to comprehending the abstract and contextual idea of the sine rule. The study's conclusions highlight how crucial it is to use problem-based learning models while teaching mathematics in order to promote student participation and the growth of higher-order thinking abilities. This study contributes both theoretically and practically to the creation of cutting-edge mathematics education that is pertinent to the needs of the twenty-first century